Flexibilidade e capacidade cardiorrespiratória em crianças e adolescentes - Batista, Kenia Rejane de Oliveira (2018)
Introduction: Physical fitness related to health is considered an indicator of health, both in childhood and in adolescence, being widely associated with the reduction of health risk. Objective: to analyze the behavior of physical fitness components flexibility and cardiopulmonary fitness in children and adolescents. Methodology: The study was divided in two stages organized as follows: the first one was to analyze the existing evidence regarding the physical capacity flexibility in Brazilian children and adolescents, based on a Systematic Review carried out on studies in Brazil. The second stage consists of a manuscript that aimed to verify the behavior of cardiorespiratory capacity, according to age group and sex, in children and adolescents of the Northeast Region of Brazil. Results: the first manuscript shows that, apparently, flexibility is not adequately analyzed in the studies, since it has been treated as a coadjuvant suggesting the masking of its real importance. When analyzing these studies, it was evidenced that there is a lack of information regarding the adequate use of flexibility in the references of the works, since there is no comparison with a reference standard. The second manuscript indicated that, in the age group up to 13 years of age, the behavior of cardiorespiratory fitness was random in both sexes. For the age group above 13 years of age, the behavior of cardiorespiratory fitness tends to grow in both sexes, but in the female sex, it is limited until the age of 17 years. Males presented higher values at all ages when compared to the opposite sex. Conclusion: it may be necessary to map physical fitness levels with children and adolescents in Brazil, using the results to create a benchmark for physical fitness.